Antibacterial and antibiofilm activity of Eucalyptus globulus leaf extract, asiatic acid and ursolic acid against bacteria isolated from bovine mastitis - Mezzasalma, Nicolò; Spadini, Costanza; Spaggiari, Chiara; Annunziato, Giannamaria; Andreoli, Valentina; Prosperi, Alice; Mochen, Lorenzo; Cavirani, Sandro; Grolli, Stefano; Taddei, Simone; Costantino, Gabriele; Cabassi, Clotilde Silvia (Frontiers in Veterinary Science, 2025)
Antibiotics represent the first line therapy for bovine mastitis. However, the increasing prevalence of multidrug-resistant organisms (MDROs) highlights the need for alternative therapeutic approaches. This study evaluated the antimicrobial and antibiofilm activities of Eucalyptus globulus leaf extract (EGL-L), ursolic acid (UA) and asiatic acid (AA) against Staphylococcus aureus (SA), Streptococcus uberis (SU), Streptococcus agalactiae (SAG), and Enterococcus spp. (EN) isolated from bovine mastitis, 39.7% of which were MDROs. The minimal inhibitory concentration (MIC) assay demonstrated that all the compounds exhibited antimicrobial activity against the tested bacteria, including MDROs. However, EGL-L was less effective (p < 0.001) than UA or AA against field strains. UA was more effective against SAG and SU compared to SA (p < 0.001), whereas AA was more effective against SU than SA (p < 0.001). Conversely, EGL-L exhibited similar inhibitory effects on all bacteria. The biofilm-forming ability of the bacterial strains was also assessed, and the minimal biofilm inhibitory concentrations (MBICs) of the compounds were evaluated for moderate and strong biofilm producers. None of the compounds were able to completely inhibit biofilm formation. However, MBIC80 values within the tested concentration range were achieved for 15 out of 32 strains with EGL-L and for 27 out of 32 strains with UA and AA. These findings highlight a promising alternative to conventional antimicrobials for AA and UA, showing potential for topical intramammary use for the control and prevention of bovine mastitis, especially because of their efficacy against biofilm formation. Future research should focus on toxicity assessments and formulation development for potential topical administration.